Foul play? On the scale and scope of industrial subsidies in China - Frank Bickenbach; Dirk Dohse; Rolf J. Langhammer; Wan-hsin Liu (Kiel Institute for the World Economy (IfW Kiel), 2024)
China makes extensive use of subsidies in order to take a leading role on the global markets in the green technology sectors of electric vehicles, wind turbines and railway rolling stock. According to DiPippo et al. (2022) and recent OECD studies, the industrial subsidies in China are at least three to four times or even up to nine times higher than in the major EU and OECD countries. According to a very conservative estimate, industrial subsidies in China amounted to around EUR 221 billion or 1.73% of Chinese GDP in 2019. According to recent data of 2022, direct government subsidies for some of the dominant Chinese manufacturers of green technology products had also increased significantly - the electric car manufacturer BYD alone received EUR 2.1 billion. The authors point out that Chinese companies are benefiting from further support measures, including subsidized inputs, preferential access to critical raw materials, forced technology transfers, the strategic use of public procurement and the preferential treatment of domestic firms in administrative procedures. The authors recommend the EU to use its anti-subsidy proceeding against BEV imports from China to enter into negotiations with the Chinese government and persuade it to abolish public support measures that are particularly harmful to the EU. – – China setzt in großem Umfang Subventionen ein, um auch bei den grünen Technologiebranchen Elektrofahrzeuge, Windturbinen und Schienenfahrzeuge eine Führungsrolle auf den Weltmärkten einzunehmen. Die Industriesubventionen in China sind nach DiPippo et al. (2022) und aktuellen OECD Studien um das Drei- bis Vierfache bzw. bis hin zum Neunfachen höher als in den großen EU- und OECD-Ländern. Nach einer konservativen Schätzung beliefen sich die Industriesubventionen in China im Jahr 2019 auf rund 221 Mrd. Euro oder 1,73 Prozent des chinesischen BIP. Am aktuellen Rand des Jahres 2022 waren zudem die direkten staatlichen Subventionen für einige der dominierenden chinesischen Hersteller grüner Technologieprodukte deutlich gestiegen - allein der Elektroautohersteller BYD erhielt 2,1 Mrd. Euro. Die Autoren weisen darauf hin, dass die chinesischen Unternehmen von weiteren Unterstützungsmaßnahmen profitieren. Dazu zählen: Subventionierte Vorleistungen, der bevorzugte Zugang zu kritischen Rohstoffen, einem teils erzwungenen Technologietransfer und die Vorzugsbehandlung einheimischer Unternehmen in öffentlichen Vergabe- und Verwaltungsverfahren. Die Autoren empfehlen der EU, das laufende Antisubventionsverfahren gegen Elektroauto-Importe aus China zu nutzen, um mit der chinesischen Regierung in Verhandlungen einzutreten und sie zur Abschaffung von Subventionen zu bewegen, die für die EU besonders schädlich sind.
Keywords: 330; China; industrial subsidies; battery electric vehicles; wind turbines; railway rolling stock; EU anti-subsidy proceeding; China; Industriesubventionen; Batteriebetriebene Elektrofahrzeuge; Windturbinen; Schienenfahrzeuge; Antisubventionsverfahren der EU